210k views
1 vote
The function gx is defined as gx=6x^2+23x-4,when does g(x)=0

2 Answers

3 votes

The given function is


g(x) = 6x^2 +23x-4

And we have to find the value of g(0), and for that we put 0 for x in the given equation.

And on substituting 0 for x in the given expression, we will get


g(0) = 6(0)^2 +23(0) -4


g(0) = 0 + 0 -4 = -4

So for the given function, the value of g(0) is -4 .

User Aidis
by
5.8k points
6 votes

For this case we have the following function:


g (x) = 6x ^ 2 + 23x-4

What we must do is find the zeros of the function.

We have then:


6x ^ 2 + 23x-4 = 0

Factoring we have:


(x + 4) (6x-1) = 0

From here, we solve the solutions of the equation:

Solution 1:


x + 4 = 0  x = -4

Solution 2:


6x-1 = 0


x = (1)/(6)

Answer:

The values of x that make the equation equal to zero are:


x = -4


x = (1)/(6)

User Jaekie
by
5.1k points